2017
DOI: 10.33607/bjshs.v4i107.38
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Oxygenation During Exercise in Physically Active and Overweight 6–19-Year-Old Children

Abstract: Background. The purpose of our study was to compare muscle oxygenation during walking exercise in physically active, non-physically active normal weight and overweight 6–19- year-old children. Methods. Twenty four normal weight, physically non-active (NPA), 27 normal weight physically active (PA) and 17 overweight (OW) 6–19-year-old children participated in this study. Muscle oxygenation was recorded by near infrared spectroscopy during constant (6 min, 6 km/h, 4% grade) and increasing walking exercise (modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The study result might have been skewed by limitations and small study size and therefore may not be enough to reach a general conclusion. Other studies suggested that childhood obesity is linked to OSAS/OSA although the pathophysiology has not been elucidated and obese children with OSAS present more severely and require expert clinical management (28,31). Furthermore, increased chest and abdominal wall weight in obese children result in decreased lung volume ad expiratory flow when subjected to submaximal exercise which further increase inactivity and the risk of other complications as a result of low oxygen saturation (28).…”
Section: Respiratory Systemmentioning
confidence: 99%
“…The study result might have been skewed by limitations and small study size and therefore may not be enough to reach a general conclusion. Other studies suggested that childhood obesity is linked to OSAS/OSA although the pathophysiology has not been elucidated and obese children with OSAS present more severely and require expert clinical management (28,31). Furthermore, increased chest and abdominal wall weight in obese children result in decreased lung volume ad expiratory flow when subjected to submaximal exercise which further increase inactivity and the risk of other complications as a result of low oxygen saturation (28).…”
Section: Respiratory Systemmentioning
confidence: 99%